2015
DOI: 10.1002/bdm.1862
|View full text |Cite
|
Sign up to set email alerts
|

Double Reference Points: the Effects of Social and Financial Reference Points on Decisions Under Risk

Abstract: The existing literature is inconsistent about how social comparison affects risk attitudes. We propose a framework where the total utility is composed of the social and financial utilities. The financial utility is consistent with prospect theory (i.e., an S-shaped utility function with a financial reference point), whereas the social utility is affected by both social and financial reference points. Therefore, social risk attitudes are determined by interaction between gains/losses in both social and financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
(54 reference statements)
1
12
0
Order By: Relevance
“…In addition, we observed that the impact of SRPs on risk-seeking behavior can be significantly manipulated by the size of the comparison group. In the case of single other and class comparisons, participants generally tended to be risk-seeking under L-SRP, in line with the findings of Lu et al (2015) . However, this risk-seeking inclination dropped dramatically in the case of school comparisons, with risky behavior reversed under L-SRP.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, we observed that the impact of SRPs on risk-seeking behavior can be significantly manipulated by the size of the comparison group. In the case of single other and class comparisons, participants generally tended to be risk-seeking under L-SRP, in line with the findings of Lu et al (2015) . However, this risk-seeking inclination dropped dramatically in the case of school comparisons, with risky behavior reversed under L-SRP.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies examining the influence of SRPs on risky decision making have tended to focus on the realm of monetary decision making (stock investment, lottery, salary etc. ; e.g., Fox and Dayan, 2004 ; Linde and Sonnemans, 2012 ; Lu et al, 2015 ). According to Xie and Lu (2014) , these SRPs can be divided into three types: social gain, social loss, and social neutral.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many studies have begun to emphasize the role of social comparison. For instance, Lu et al [ 47 ] demonstrated that insecurity occurs when individuals are faced with adverse social comparison results, while Cotier and Toulopoulou [ 15 ] further emphasized that negative social comparison appears to be a potential sign of depression. Thus, helping adolescents acquire appropriate social comparison methods could not only be conducive to their social decision-making, but also benefit their physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Beside social reference points, they consider an individual's present financial position as a financial reference point. Lu et al (2015) state that individuals think about the financial reference point(s) firstly, and then social reference points are considered. Thus, based on an evolutionary perspective, the safety-first principle is valid (Wang & Johnson, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%